Spin Frustrated Pyrazolato Triangular Cuii Complex: Structure and Magnetic Properties, an Overview - Spencer-Ossa, E; Venegas-Yazigi, D; Venegas-Yazigi, D; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P; Paredes-Garcia, V (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The synthesis and structural characterization of a new triangular Cu3–μ3OH pyrazolato complex of formula, [Cu3(μ3−OH)(pz)3(Hpz)3][BF4]2 (1−Cu3), Hpz = pyrazole, is presented. The triangular unit forms a quasi-isosceles triangle with Cu–Cu distances of 3.3739(9), 3.3571(9), and 3.370(1) Å. This complex is isostructural to the hexanuclear complex [Cu3(μ3−OH)(pz)3(Hpz)3](ClO4)2]2 (QOPJIP). A comparative structural analysis with other reported triangular Cu3–μ3OH pyrazolato complexes has been carried out, showing that, depending on the pyrazolato derivative, an auxiliary ligand or counter-anion can affect the nuclearity and/or the dimensionality of the system. The magnetic properties of 1−Cu3 are analyzed using experimental data and DFT calculation. A detailed analysis was performed on the magnetic properties, comparing experimental and theoretical data of other molecular triangular Cu3–μ3OH complexes, showing that the displacement of the μ3−OH− from the Cu3 plane, together with the type of organic ligands, influences the nature of the magnetic exchange interaction between the spin-carrier centers, since it affects the overlap of the magnetic orbitals involved in the exchange pathways. Finally, a detailed comparison of the magnetic properties of 1−Cu3 and QOPJIP was carried out, which allowed us to understand the differences in their magnetic properties. © 2023 by the authors.